A survey among physicians in surgery and anesthesiology departments after the first surge of SARS-CoV-2 infections in Germany Preparing for further challenges ahead - Grishina, Anna; Link, Fabian; Arend, Arne; Kleemann, Florentine; Tober-Lau, Pinkus; Andree, Dominik; Muenn, Friederike; Gruendl, Magdalena; Quante, Markus; Lederhuber, Hans; Albertsmeier, Markus; Struller, Florian; et al. (Wiener Klinische Wochenschrift, 2022)
Background The SARS-CoV-2 pandemic has extensively challenged healthcare systems all over the world. Many elective operations were postponed or cancelled, changing priorities and workflows in surgery departments. Aims The primary aim of this cross-sectional study was to assess the workload and psychosocial burden of surgeons and anesthesiologists, working in German hospitals during the first wave of SARS-CoV-2 infections in 2020. Methods Quantitative online survey on the workplace situation including psychosocial and work-related stress factors among resident and board-certified surgeons and anesthesiologists. Physicians in German hospitals across all levels of healthcare were contacted via departments, professional associations and social media posts. Results Among 154 total study participants, 54% of respondents stated a lack of personal protective equipment in their own wards and 56% reported increased staff shortages since the onset of the pandemic. While routine practice was reported as fully resumed in 71% of surgery departments at the time of the survey, work-related dissatisfaction among responding surgeons and anesthesiologists increased from 24% before the pandemic to 36% after the first wave of infections. As a countermeasure, 94% of participants deemed the establishment of action plans to increase pandemic preparedness and strengthening German public health systems a useful measure to respond to current challenges. Conclusion The aftermath of the first wave of SARS-CoV-2 infections in Germany has left the surgical staff strained, despite temporarily decreased workloads. Overall, a critical review of the altered conditions is indispensable to identify and promote effective solutions and prudent action plans required to address imminent challenges.
CRIS-Team WoS Importer:2022-01-28